Mobile‐aware dynamic resource management for edge computing - Filiposka, Sonja; Mishev, Anastas; Gilly, Katja (Wiley, 2019)
Shifting cloud computing capabilities close to the edge enables provisioning of low latency location-based Internet services that are adapted to user behaviour. However, this can be achieved neither with a simple move of the physical hosts closer to edge networks, nor continuing to abide by the same principles as the ones implemented in traditional cloud computing approaches. In order to accomplish the promised high quality of service, changes must be made to the resource management techniques so that they are adapted to the requirements of fog computing. This paper introduces a novel location-based handoff management and its corresponding implementation of dynamic resource management modules that introduce resource allocation and migration strategies adapted specifically to fog computing. The aim is the implementation of the follow-me behaviour of edge resources considering a tightly coupled perspective with the user location. The proposal is based on the concept of mapping physical areas to logical resource communities while triggering migration of resources to the corresponding logical community when mobile nodes move from the boundaries of one physical area to another. The results analysis from the simulation-based scenarios shows that the effectiveness of our community-based dynamic resource management proposal in following the geographical trajectory of mobile users with wearable devices is over 90% and that it copes very well for highly saturated environments. The comparison with traditional resource management techniques clearly presents the advantages of our proposal, while the parameter wise in-depth analysis discusses its dependencies on the number of mobile nodes, speed, and available resources.
Keywords: Edge/fog computing, wireless access, dynamic resource management, node mobility, handoff